2017
DOI: 10.7454/psr.v4i1.3660
|View full text |Cite
|
Sign up to set email alerts
|

Parameter Fisikokimia dan Analisis Kadar Allyl Disulfide dalam Ekstrak Etanol 70% Bawang Putih (Allium sativum L.) dengan Perbandingan Daerah Tempat Tumbuh

Abstract: AbstrakBawang putih (Allium sativum L.) merupakan salah satu tanaman obat yang potensial untuk dikembangkan menjadi obat tradisional. Produk obat tradisional dan tanaman obat yang berkualitas ditentukan salah satunya oleh mutu dan keamanan ekstrak. Faktor yang dapat mempengaruhi mutu salah satunya adalah daerah tempat tumbuh. Penelitian ini bertujuan untuk membandingkan beberapa nilai parameter fisikokimia serta kadar senyawa yang bertanggung jawab atas aktivitas farmakologis dalam ekstrak etanol 70% bawang pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
0
3
0
1
Order By: Relevance
“…Yield extraction results can be influenced by several factors, including biological factors and chemical factors. The biological factors include harvesting time, location of growth, plant species and plant parts used while the chemical factors include extraction methods, size, hardness, dryness of the material, type of solvent used, and types and levels of active compounds contained in plant material (Prastiwi et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Yield extraction results can be influenced by several factors, including biological factors and chemical factors. The biological factors include harvesting time, location of growth, plant species and plant parts used while the chemical factors include extraction methods, size, hardness, dryness of the material, type of solvent used, and types and levels of active compounds contained in plant material (Prastiwi et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Di dalam Bawang putih terdapat allicin yaitu zat bioaktif yang mudah menguap dengan kandungan sulfur dan mempunyai aktivitas antibakteri dan antijamur. Penggunaan bawang putih secara langsung dapat mengiritasi kulit dan memiliki bau yang tidak enak (7,8) . Bawang putih juga mengandung fitosterol turunan fenolik dan senyawa sulfur alil yang larut dalam lemak, serta flavonoid, alkaloid dan saponin memiliki aktivitas penyubur rambut yang diaplikasikan secara topical pada pasien Alopecia (9,10) .…”
Section: Pendahuluanunclassified
“…Sulfide derivatives, namely allicin, are stomach poisons that kill the target organism if allicin enters the digestive organs and is absorbed by the intestinal wall (7). Allicin is produced from alliin and alliinase enzymes formed after the processing of Allium sativum, and it is very reactive and unstable (19). This instability causes allicin to turn into a compound of allyl disulfide, which is classified as an organic synthetic pesticide (7,19) and inhibits or blocks the action of the cholinesterase and ganglion enzymes in the central nervous system terminal (7).…”
Section: Allium Sativum Effectiveness Testmentioning
confidence: 99%
“…Some conditions that affected the differences of number of died insects from each concentration were differences in the insect sensitivity to the solution concentrations, the condition of each insect when test materials were given and when samples were taken, the environmental conditions such as the temperature at which experiment was conducted, extract storage (4,25), the extract quality (test material) which was affected by plant species, plant age, parts used, and etc. (19) The results of research conducted by Alzowahi, et al (25) showed that there were differences in the ability of Allium sativum as an antibacterial that were °s tored at 4°C and room temperature of 30 C. The essential oil will evaporate and will be followed by an oxidation process that affects the quality if it is placed uncovered during the storage process (19).…”
Section: Allium Sativum Effectiveness Testmentioning
confidence: 99%